Analisis Peran Digital Marketing Dalam Meningkatkan Volume Penjualan Pada PT. Mondelez Indonesia Di Medan - Dara AlFira; Ngatno Sahputra; Al Firah (Universitas Dharmawangsa, 2026)
ABSTRACT - This research aims to analyze the role of digital marketing in increasing sales volume at PT. Mondelez Indonesia in Medan. This research uses a qualitative approach with data collection techniques through interviews, observation and documentation. Data analysis techniques are carried out through the stages of data reduction, data presentation, and drawing conclusions. The research results show that digital marketing plays a role in increasing the sales volume of PT products. Mondelez Indonesia, through the use of social media and marketplace platforms such as Shopee, the company is able to expand its marketing reach, increase brand awareness and attract consumer buying interest. The Shopee platform is one of the digital media that makes the largest contribution to sales of company products. However, its implementation has experienced several obstacles, such as the uneven level of consumer involvement, high levels of competition, and the use of digital data that has not been optimal in analyzing consumer behavior. Therefore, companies need to increase creativity in creating digital content, maximize the use of consumer data, and strengthen promotional strategies through various digital platforms so that the implementation of digital marketing can be more effective in increasing product sales volume.